Diversity and structure of soil fungal communities unveil the building history of a burial mound of ancient Japan (Tobiotsuka Kofun, Okayama Prefecture). (October 2022) - Voyron, Samuele; Tonon, Chiara; Guglielmone, Laura; Celi, Luisella; Comina, Cesare; Ikeda, Hajime; Matsumoto, Naoko; Petrella, Daniele; Ryan, Joseph; Sato, Kazuhiro; Seike, Akira; Varriale, Ivan; et al.
Abstract: Kofuns are burial mounds of ancient Japan (3rd-7th century CE, defined as Kofun Period). The construction history and archaeological significance of Kofuns of the Late Kofun Period (6th-7th century) still need to be characterized. This study dealt with Tobiotsuka Kofun (Okayama Prefecture, Japan) and aimed to investigate if diversity and structure of soil fungal communities, and their relationships with soil characteristics, beyond reflecting present vegetation, may be informative on the construction history of the burial mound. In particular the analyses aimed to verify the supposed presence of a boundary between the original hill and the potential anthropic backfill. Soil fungal communities were characterized by high-throughput sequencing (Illumina MiSeq technology), at the ground and through different archaeological soil layers. Approximately 1.5 × 10 6 high quality ITS2 sequences, clustered in 1875 OTUs, were obtained from 59 sampling points, distributed inside the burial chamber and on the Kofun external slopes. Heterogeneity and vertical distribution of fungal communities, considered in terms of taxonomic and trophic groups, generally showed a compatible pattern with present-day topographic conditions and vegetation. However, the chemical soil analyses and fungal distribution with depth, in particular that of saprotrophic fungi, cannot be explained by natural soil development and ecological context only, and point towards the presence of a former topsoil layer that was disturbed and at least partially buried by the Kofun construction. Highlights: Metabarcoding of soil fungi highlighted the building history of a burial mound. Communities at the ground level and in archaeological layers significantly diverged. Taxonomic and trophic profiles were mostly compatible with present vegetation. Depth distribution of saprotrophs and C contents indicated a buried, former topsoil. Dominance of Ascomycota suggested an agricultural origin of anthropogenic soil layers.